2020
DOI: 10.3390/nano10050875
|View full text |Cite
|
Sign up to set email alerts
|

Bone Diseases: Current Approach and Future Perspectives in Drug Delivery Systems for Bone Targeted Therapeutics

Abstract: Bone diseases include a wide group of skeletal-related disorders that cause mobility limitations and mortality. In some cases, e.g., in osteosarcoma (OS) and metastatic bone cancer, current treatments are not fully effective, mainly due to low patient compliance and to adverse side effects. To overcome these drawbacks, nanotechnology is currently under study as a potential strategy allowing specific drug release kinetics and enhancing bone regeneration. Polymers, ceramics, semiconductors, metals, and self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 156 publications
(172 reference statements)
0
36
0
Order By: Relevance
“…However, highly efficacious agents with outstanding safety and efficacy are necessary. Extensive studies has been carried out in the past few decades to understand osteoblast differentiation and bone formation, and the drug discovery research continued their effort to develop new therapeutic agents that can prevent and/or treat bone diseases [ 4 , 5 , 6 ]. Further, previous studies suggested that metabolic dysfunction and osteoporosis share common pathways, which include the regulation of calcium homeostasis, receptor activator of nuclear factor-kappa B (NF-κB) ligand (RANKL), osteoprotegerin, and Wnt-β-catenin signaling pathways [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, highly efficacious agents with outstanding safety and efficacy are necessary. Extensive studies has been carried out in the past few decades to understand osteoblast differentiation and bone formation, and the drug discovery research continued their effort to develop new therapeutic agents that can prevent and/or treat bone diseases [ 4 , 5 , 6 ]. Further, previous studies suggested that metabolic dysfunction and osteoporosis share common pathways, which include the regulation of calcium homeostasis, receptor activator of nuclear factor-kappa B (NF-κB) ligand (RANKL), osteoprotegerin, and Wnt-β-catenin signaling pathways [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of medical science and technology, the rate of limb salvage in osteosarcoma is greater than 80% in the clinic, and limb salvage has gradually replaced amputation in the majority of cases (18). Currently, the widely accepted strategy for osteosarcoma treatment is surgery combined with neoadjuvant chemotherapy (19,20). Different chemotherapy regimens include the use of two to seven drugs, of which the four classic drugs that show consistent effects are cisplatin, doxorubicin, and high-dose methotrexate with leucovorin and ifosfamide with or without etoposide (21).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs and therapeutic strategies are currently available for common bone disorders occurring due to increased bone resorption like osteoporosis, bone metastasis, osteosarcoma, osteoarthritis, and Paget’s disease. 76 These broadly include bone-targeted anti-resorptive drugs like bisphosphonates (BPs), 77 , 78 antibody treatment, 79 combination anti-resorptive therapy, 80 , 81 antibiotics like tetracyclines, 82 chemotherapeutic agents 83 , 84 and hormonal therapy. 85 The Food and Drug Administration (FDA) approved anti-resorptive drugs BPs, 86 such as alendronate, risedronate, ibandronate and zoledronic acid, are used to treat osteoporosis, 87 , 88 bone metastases 89 , 90 and osteosarcoma 91 , 92 by inhibiting bone demineralization 93 , 94 and tumor growth.…”
Section: The Clinical Need For Drug Delivery Systems To Bonementioning
confidence: 99%